2016
DOI: 10.1038/cddis.2016.111
|View full text |Cite
|
Sign up to set email alerts
|

'Mitochondrial energy imbalance and lipid peroxidation cause cell death in Friedreich’s ataxia'

Abstract: Friedreich's ataxia (FRDA) is an inherited neurodegenerative disease. The mutation consists of a GAA repeat expansion within the FXN gene, which downregulates frataxin, leading to abnormal mitochondrial iron accumulation, which may in turn cause changes in mitochondrial function. Although, many studies of FRDA patients and mouse models have been conducted in the past two decades, the role of frataxin in mitochondrial pathophysiology remains elusive. Are the mitochondrial abnormalities only a side effect of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(103 citation statements)
references
References 51 publications
5
94
0
1
Order By: Relevance
“…FRDA's GAA expansion mutation leads to deficiency of the frataxin protein, causing mitochondrial dysfunction through promoting ROS production . Recently, studies by Abeti et al revealed that FRDA mouse models show a decrease in mitochondrial membrane potential that is caused by an activity imbalance between Complex I and II in the electron transport chain. This imbalance causes ROS generation in the mitochondrial intermembrane space and the matrix, and the subsequent lipid peroxidation results in neuron degeneration.…”
Section: Mitochondrial Abnormalities Lead To Neurodegenerative Diseasesmentioning
confidence: 99%
“…FRDA's GAA expansion mutation leads to deficiency of the frataxin protein, causing mitochondrial dysfunction through promoting ROS production . Recently, studies by Abeti et al revealed that FRDA mouse models show a decrease in mitochondrial membrane potential that is caused by an activity imbalance between Complex I and II in the electron transport chain. This imbalance causes ROS generation in the mitochondrial intermembrane space and the matrix, and the subsequent lipid peroxidation results in neuron degeneration.…”
Section: Mitochondrial Abnormalities Lead To Neurodegenerative Diseasesmentioning
confidence: 99%
“…Characterization of the YG8 and YG8sR models, carrying FXN exogenous genes with 90 + 190 or 200 GAA repeats, respectively, showed age‐dependent FRDA symptoms such as ambulatory difficulties, decreased frataxin mRNA levels, abnormal root ganglia, reduced aconitase activity and oxidative stress . Neurons derived from the YG8 mouse also showed a reduction in Complex I activity, increased oxidative stress in both mitochondria and cytosol, and lipid peroxidation . These models, in addition to recapitulating the characteristic FRDA phenotype, were also suitable for studying the genetic aspects of the disease, such as GAA repeat instability , gene silencing induced by the expansion and novel gene therapy approaches .…”
Section: Mice Modelsmentioning
confidence: 99%
“…Detailed mechanism of peroxyl radical addition reactions has been discussed by Xu et al [2]. Lipid peroxidation in vivo has been linked to the underlying pathophysiology of various disease states, including atherosclerosis, myocardial ischemia-reperfusion injury, diabetes, cancer, and neurodegenerative injury [3-7]. …”
Section: Introductionmentioning
confidence: 99%